Biotransformation of Indole to 3-Methylindole by Lysinibacillus xylanilyticus Strain MA - Pankaj Kumar Arora; Kartik Dhar; Rafael Alejandro Veloz García; Ashutosh Sharma (Journal of Chemistry)
An indole-biotransforming strain MA was identified as Lysinibacillus xylanilyticus on the basis of the 16S rRNA gene sequencing. It transforms indole completely from the broth culture in the presence of an additional carbon source (i.e., sodium succinate). Gas-chromatography-mass spectrometry identified indole-3-acetamide, indole-3-acetic acid, and 3-methylindole as transformation products. Tryptophan-2-monooxygenase activity was detected in the crude extracts of indole-induced cells of strain MA, which confirms the formation of indole-3-acetamide from tryptophan in the degradation pathway of indole. On the basis of identified metabolites and enzyme assay, we have proposed a new transformation pathway for indole degradation. Indole was first transformed to indole-3-acetamide via tryptophan. Indole-3-acetamide was then transformed to indole-3-acetic acid that was decarboxylated to 3-methylindole. This is the first report of a 3-methylindole synthesis via the degradation pathway of indole.